2015
DOI: 10.1016/j.neuroscience.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vesicular glutamate transporters in transient receptor potential melastatin 8 (TRPM8)-positive dental afferents in the mouse

Abstract: Transient receptor potential melastatin 8 (TRPM8) is activated by innocuous cool and noxious cold and plays a crucial role in cold-induced acute pain and pain hypersensitivity. To help understand the mechanism of TRPM8-mediated cold perception under normal and pathologic conditions, we used light microscopic immunohistochemistry and Western blot analysis in mice expressing a genetically encoded axonal tracer in TRPM8-positive (+) neurons. We investigated the coexpression of TRPM8 and vesicular glutamate transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Considering that both VGLUT2 and TRPM8 in the primary sensory neurons have been implicated in the mediation of acute nociceptive and pathologic pain [68,69], it seems likely that VGLUT2-mediated glutamate signaling is involved in the transmission of TRPM8-mediated noxious cold. Furthermore, the expression of VGLUT2 in TG neurons is upregulated following pulpal inflammation, whereas the expression of TRPM8 is not significantly changed [7]. Since both TRPM8 and VGLUT2 are implicated in cold hypersensitivity following inflammation [69][70][71], it is reasonable to assume that cold hypersensitivity following pulpal inflammation is induced by upregulation of the expression of VGLUT2 in the TRPM8-expressing TG neurons, rather than by the direct effect of TRPM8 upregulation.…”
Section: Expression Of Vglut In the Tg Neurons And Pulpal Axons That mentioning
confidence: 99%
See 4 more Smart Citations
“…Considering that both VGLUT2 and TRPM8 in the primary sensory neurons have been implicated in the mediation of acute nociceptive and pathologic pain [68,69], it seems likely that VGLUT2-mediated glutamate signaling is involved in the transmission of TRPM8-mediated noxious cold. Furthermore, the expression of VGLUT2 in TG neurons is upregulated following pulpal inflammation, whereas the expression of TRPM8 is not significantly changed [7]. Since both TRPM8 and VGLUT2 are implicated in cold hypersensitivity following inflammation [69][70][71], it is reasonable to assume that cold hypersensitivity following pulpal inflammation is induced by upregulation of the expression of VGLUT2 in the TRPM8-expressing TG neurons, rather than by the direct effect of TRPM8 upregulation.…”
Section: Expression Of Vglut In the Tg Neurons And Pulpal Axons That mentioning
confidence: 99%
“…Recent immunohistochemical studies showed the distribution of coldsensing channels TRPA1 and TRPM8 in the axons of dental pulp [7,22]: thus, nerve fibers expressing TRPA1 and/or TRPM8 are scant in the radicular pulp and the core of the coronal pulp, but they branch extensively and form a network of fibers in the peripheral pulp: many TRPM8-positive axons were also found to penetrate the dentinal tubules toward the enamel. The latter observation, in particular, may have clinical implications since it indicates that the TRPA1-and TRPM8-mediated pain from noxious cold is primarily perceived at the level of the peripheral pulp and dentin.…”
Section: Expression and Distribution Of Receptors And Ion Channels Inmentioning
confidence: 99%
See 3 more Smart Citations